Sentinel-2 Reveals Abrupt Increment of Total Suspended Matter While Ever Given Ship Blocked the Suez Canal - Milad Niroumand-Jadidi (MDPI AG, 2021)
The blockage of the Suez Canal, one of the world’s key trade routes, by a giant container ship in March 2021 was in the spotlight of news media worldwide, mainly because of its economic impacts. In this study, we look at this event from an environmental perspective by analyzing the impact of the artificial barrier made by the ship over the channel and of operations like dredging on the concentration of total suspended matter (TSM). In this context, multitemporal Sentinel-2 images are used to study short-term variations of TSM within a time window spanning before, during, and after the blockage event. A well-established neural network-based processor called Case 2 Regional CoastColour (C2RCC) is employed to derive remote sensing reflectance (Rrs) and then TSM concentrations from Sentinel-2 imagery. The results indicate that the stuck ship acted as an artificial barrier leading to very different TSM conditions north and south of the canal. Furthermore, the blockage of the Suez Canal and subsequent dredging caused an abrupt increment (+400%) in the concentration of TSM moving north from the ship’s location. We also identified a very high contrast between the TSM concentration in the north and south of the vessel during the blockage event.